Reimagining Music Teacher Collaboration: The Culture of Professional Learning Communities as Professional Development Within Schools and Districts. (October 2019) - Battersby, Sharyn L.
Music educators are continually seeking new ways to better their practice and improve student learning. Professional learning communities are a type of collaborative community that when administered successfully provide a forum for music educators to become active participants in both their own learning and that of their students. While the notion of professional learning communities has been around since the 1990s, they have received renewed attention more recently due to the adaptation and implementation of Danielson's popular Framework for Teaching, which has been implemented in many school districts across the country. Teachers facing the challenge of reshaping the culture of their music programs and seeing their initiative sustained will devise elements that will become embedded in that (school) culture. Supportive and shared leadership, shared values and vision, and collective learning are just some of the attributes that can contribute to student learning and the professional development of music teachers.